THE INFLUENCE OF FINANCIAL SOCIALIZATION, FINANCIAL EXPERIENCE, AND FINANCIAL LITERACY ON INVESTMENT INTENTION - Hilwa Salsa Bila; Dicky Jhoansyah; Faizal Mulia Z (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
The rapid advancement of technology has made it easier for individuals to carry out various activities, including investing. Amid the current weakening of Indonesia’s Composite Stock Price Index (IHSG), an increase in public investment interest is expected to contribute positively to the national economy. Generation Z, as digital natives, holds significant potential in the development of the investment sector. This study aims to analyze the influence of financial socialization, financial experience, and financial literacy on investment intention among Generation Z in Sukabumi City. A quantitative approach with an associative method was employed in this research. Data were collected using purposive sampling, involving 170 respondents categorized as members of Generation Z. The data were analyzed using multiple linear regression analysis. The results reveal that financial socialization does not significantly influence investment intention, indicating that social interaction or exposure alone may not be sufficient to drive investment behavior among Generation Z. In contrast, financial experience has a positive and significant effect on investment intention. Similarly, financial literacy also shows a positive and significant effect on investment intention among Generation Z. These findings suggest that financial experience and financial literacy play crucial roles in shaping individuals' intentions to invest. Therefore, stakeholders are encouraged to enhance financial education programs and provide more practical financial experiences to increase investment interest among younger generations, particularly Generation Z.